Light-activatable TET-dioxygenases reveal dynamics of 5-Methylcytosine oxidation and transcriptome reorganization - Palei, Shubhendu; Buchmuller, Benjamin; Wolffgramm, Jan; Muñoz-Lopez, Álvaro; Jung, Sascha; Czodrowski, Paul; Summerer, Daniel (Technische Universität Dortmund, 2020)
Ten-eleven-translocation (TET) dioxygenases catalyze the oxidation of 5-methylcytosine (5mC), the central epigenetic regulator of mammalian DNA. This activity dy- namically reshapes epigenome and transcriptome by deposit- ing oxidized 5mC derivatives, and initiating active DNA de- methylation. However, studying this dynamic is hampered by the inability to selectively activate individual TETs with tem- poral control in cells. We report activation of TETs in mam- malian cells by incorporation of genetically encoded 4,5- dimethoxy-2-nitrobenzyl-L-serine as transient active site block, and its subsequent deprotection with light. Our ap- proach enables precise insights into the impact of cancer- associated TET2 mutations on the kinetics of TET2 catalysis in vivo, and allows time-resolved monitoring of target gene activation and transcriptome reorganization. This sets a basis for dissecting the order and kinetics of chromatin-associated events triggered by TET catalysis, ranging from DNA de- methylation to chromatin and transcription regulation.
Keywords: 570; 540